Merdeka Curriculum: Early Childhood Teachers' Perceptions of the New Paradigm Curriculum - Ariq Nurjannah Irbah; I’in Anggryani; Ucik Hidayah Binsa (Child Kingdom : Jurnal Pendidikan Anak Usia Dini, 2024)
This research aims to obtain information regarding teachers' perceptions of the independent curriculum in early childhood education. The method used in this research is a qualitative descriptive method, namely a method that explores the situation and data of the subject that will be studied thoroughly, broadly and in depth. This research provides an overview and explanation of teachers' perceptions of the independent curriculum in Paron District. The data collection technique used was interviews via questionnaires. Then the data analysis technique in this research uses reduction, display and verification techniques. The results of this research indicate that the overall perception of teachers in the independent curriculum is good. This is proven from the results of interviews via questionnaires with many expressions that support the implementation of the independent curriculum. This good and supportive perception is reflected in the teacher's knowledge of the Merdeka curriculum, the implementation of the Merdeka-merdeka play curriculum and how teachers make efforts towards the Merdeka-merdeka learning curriculum